Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/app7121244
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Fabrication of HfO2 Thin Films Passivating Si from a Numerical Computer and Remote Plasma ALD

Abstract: Recombination of charge carriers at silicon surfaces is one of the biggest loss mechanisms in crystalline silicon (c-Si) solar cells. Hafnium oxide (HfO 2 ) has attracted much attention as a passivation layer for n-type c-Si because of its positive fixed charges and thermal stability. In this study, HfO 2 films are deposited on n-type c-Si using remote plasma atomic layer deposition (RP-ALD). Post-annealing is performed using a rapid thermal processing system at different temperatures in nitrogen ambient for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…These two values of D it fall in the expected order of magnitude for passivation properties of HfO x layers, and imply effective chemical passivation. According to the literature, annealed HfO x layers result in better Q f and D it values [16,17]. The HfO x passivation layer was annealed naturally during absorber layer deposition at 540°C, in this study.…”
Section: Capacitance-voltage (C-v) Measurementmentioning
confidence: 98%
“…These two values of D it fall in the expected order of magnitude for passivation properties of HfO x layers, and imply effective chemical passivation. According to the literature, annealed HfO x layers result in better Q f and D it values [16,17]. The HfO x passivation layer was annealed naturally during absorber layer deposition at 540°C, in this study.…”
Section: Capacitance-voltage (C-v) Measurementmentioning
confidence: 98%
“…Besides, the FTIR spectra of the investigated Hf x Ta y O z films presented in Figure 7 have also displayed the detection of Hf-O chemical bondings located at 424, 465, 512, 563, 32 and 623 cm –1 , 29 29 Ta–O chemical bondings at 524, 648, 42 , 43 1150, and 1184 cm –1 , 44 as well as Ta–O–Ta chemical bonding at 660 cm –1 . 45 45 Additional chemical bondings with regard to Ta–N and Ta–O–N were detected at 784 46 and 392.2 cm –1 47 as well as at 389.2 cm –1 , 47 47 respectively, for all of the investigated Hf x Ta y O z films.…”
Section: Resultsmentioning
confidence: 81%
“…Based on the acquired accumulation level of capacitance for Hf x Ta y O z films, it was perceived that the increase of wet oxidation temperature from 600 to 1000 °C has triggered a reduction in the accumulation level of capacitance that would translate into a lower dielectric constant ( k ) value ( Figure 6 ). A substantial reduction of the accumulation level of capacitance for the Hf x Ta y O z films annealed at 1000 °C would propose an exaggeration in the formation of interfacial layer comprising a higher concentration of low- k SiO x , which could be corroborated through the detection of Si–O chemical bonding at 1108 29 and 1097 cm –1 30 as well as Si–O–Hf bonding at 872 and 895 cm –1 , 31 respectively, using Fourier transformed infrared (FTIR) measurements ( Figure 7 ). The Si–O–Hf bonding was observed only for samples subjected to wet oxidation at 600, 800, and 1000 °C, supporting that the interfacial layer formed at a temperature beyond 400 °C consisted of Hf-O-Si and SiO x .…”
Section: Resultsmentioning
confidence: 96%
“…Al 2 O 3 due to its polycrystalline nature with more grain boundary defects which leads to easier migration of Cu ions. Different previous reports already have confirmed that crystallization is favorable in case of HfO 2 , compared to Al 2 O 3 for direct deposition on Si[33,34,35,36].…”
mentioning
confidence: 61%